TEACHERS’ PERSPECTIVE ON THEIR TEACHING PROFESSIONS - Zaiturrahmi, Darlina, Mirunnisa (Jurnal Real Riset, 2021)
Teachers’ perspective about their teaching is play an important role in enhancing the teaching learning process because the strategy they belief in teaching practice influence the quality of education. This study aims at investigating teachers’ perfective about their teaching that relate to their belief and strategy in teaching process. Teachers with different background of study at senior high school level were interviewed in order to obtain the data qualitatively. The finding illustrated some teachers’ belief being patience and wisdom was important thing to avoid confrontation in classroom since every student has unique characteristics. In teaching strategy, the techniques applied by teachers should appropriate with contexts and contents of the syllabus. In order to investigate the difficulties of materials served in the classroom, reflection was done regularly. Additionally, assessment was not always applied at the end of semester; it could be done every meeting. Moreover the successful of teaching was not permanently evaluated by students’ score but also the changing of students’ behaviour and attitude.